Relações interpessoais e a perspectiva da educação inclusiva - Bissacotti, Cíntia (2023)
This Master's research was developed within the scope of the Graduate Program in Education - Federal University of Santa Maria (UFSM) and inserted in the line of research “Special Education, Inclusion and Difference”. It was funded by the Coordination for the Improvement of Higher Education Personnel (CAPES). This study is based on the assumption that interpersonal relationships are an integral and transforming part of the human being, in this sense, relationships between teachers can influence the process of school inclusion. However, working in an inclusive perspective is not an easy task, due to the great diversity of students that the school context encompasses. Thus, this study aims to understand how interpersonal relationships are established between the Special Education teacher and the teacher in the early years of Elementary School, through collaborative teaching from the perspective of school inclusion. The theoretical framework adopted in the study was based on a psychoanalytic approach to interpersonal relationships, based on authors such as Sigmund Freud (1856 –1939); Wilfred Bion (1897 – 1979) and Henri Wallon (1879 – 1962). In addition, information on the process of school inclusion based on Brazilian legislation and on authors who support inclusive education, such as: Mantoan (2003, 2007), Rabelo (2012), Vilaronga (2014), Capellini (2004) and Pereira (2009). According to the methodology, an exploratory case study was carried out with a qualitative approach, making use of semistructured interviews for data collection, addressing themes about training, interpersonal relationships and collaborative teaching, in which were answered by Special Education teachers and common school teachers in the early years of Elementary School. The analysis was performed using the Content Analysis technique, as proposed by Laurence Bardin (2011), highlighting interpersonal relationships from an inclusive perspective. Three analytical categories were identified: 1) Interpersonal relationships between professors and influence on the inclusion process. 2) Inclusive Educational Practices: collaborative teaching as a school inclusion strategy based on interpersonal relationships 3) Inclusion and teacher training in the field of Education. The research results indicated that interpersonal relationships and collaborative teaching occur through dialogues and partnerships between teachers. However, some barriers were identified, such as lack of time for collaborative planning, existing gaps in initial teacher training, high demand from students in the process of school inclusion, reduced workload of Special Education teachers at school. Thus, these factors end up hindering interpersonal relationships and the development of collaborative work from the perspective of inclusion.